(untitled) (Baghdad Science Journal, 2019)
Antibiotic resistance is a problem of deep scientific concern both in hospital and community settings. Rapid detection in clinical laboratories is essential for the judicious recognition of antimicrobial resistant organisms. So, the growth of Uropathgenic Escherichia coli (UPEC) isolates with Multidrug-resistant (MDR) and Extensively Drug-resistant (XDR) profiles that thwart therapy for (UTIs) has been detected and has straight squeezed costs and extended hospital stays. This study aims to detect MDR- and XDR-UPEC isolates. Out of 42 UPEC clinical isolates were composed from UTI patients. The bacterial strains were recognized by standard laboratory protocols. Susceptibility to antibiotic was measured by the standard disk diffusion method Out of 42 Uropathogenic E. coli, 37 (88.09%) were found to be MDR while 5 isolates (11.90%) were XDR. The present study concluded high prevalence of uropathogenic Escherichia coli (UPEC) with Multidrug-resistant (MDR) isolated from urinary tract infection in Babylon province – Iraq.